‘Reformed Pastors’ and Bons Curés: the Changing Role of the Parish Clergy in Early Modern Europe - Green, Ian (Studies in church history, 1989)
Over the last half century, a number of sociologists on both sides of the Atlantic have tried to define the contemporary role of the ministry. Among the ideas which emerged from their work, three are relevant for our purpose here. The first was that a number of roles which well-intentioned if not always well-qualified clergy had tried to play in the past had been lost or were being lost to rival professions, few of whose members were in holy orders: doctors and psychiatrists, marriage guidance counsellors and social caseworkers, solicitors and schoolteachers. Sociologists detected a sense of what was called ‘role uncertainty’ among the English clergy, and a feeling that in future they should be trained in new skills such as counselling. Allied to this disquiet was another concern, that the administrative and organizational side of the minister’s work was threatening to swamp the more important traditional roles of priest, pastor, and preacher. A third suggestion was that in an increasingly secular society the status of the ministry was declining. For centuries, it was argued, the clergy had enjoyed a unique place in society because of their sacerdotal functions and special skills, but this was now changing: the value of the Christian ministry in the eyes of the laity was falling behind that of more ‘useful’ professions such as medicine and the law.